2008
DOI: 10.1021/om700568h
|View full text |Cite
|
Sign up to set email alerts
|

Micromodulating the Electronic Coupling Across Redox-Active Ferrocenyl Spacer in Binuclear Ruthenium(II) Terpyridine Complexes: Synthesis, Electrochemistry, and Photophysical Properties

Abstract: The electrochemical and photophysical properties of [(X-tpy)RuII(tpy-(fc)2-tpy)RuII(X-tpy)]4+ (tpy = terpyridyl; X = −H (1a), −OCH3 (1b), −Cl (1c); fc = ferrocenyl) and [(X-tpy)RuII(tpy-CC-(fc)2-CC-tpy)RuII(X-tpy)]4+ (X = −H (2a), −OCH3 (2b), −Cl (2c)) are described. The ground-state HOMO and LUMO energies were probed by electrochemical measurements. The excited-state photophysical properties were probed by UV–vis absorption spectroscopy and luminescence spectroscopy. Complexes of 1a−c are nonemissive (λexc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Since the presence of the ferrocene moiety provides additional channels for the deactivation of 3 MLCT state, luminescence of the Ru(II) ferrocene-containing terpyridine complexes is almost quenched at room temperature, except for a few examples that have been reported. 2,29,31,41 Photophysical properties of 6a and 6b were studied in a H 2 O-CH 3 CN (4 : 1, v/v) solution at room temperature (Fig. 8).…”
Section: Luminescence Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the presence of the ferrocene moiety provides additional channels for the deactivation of 3 MLCT state, luminescence of the Ru(II) ferrocene-containing terpyridine complexes is almost quenched at room temperature, except for a few examples that have been reported. 2,29,31,41 Photophysical properties of 6a and 6b were studied in a H 2 O-CH 3 CN (4 : 1, v/v) solution at room temperature (Fig. 8).…”
Section: Luminescence Spectroscopymentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30] Furthermore, dinuclear transition metal complexes of bis(2,2′:6′,2′′terpyridine) ligands (T-S-T) provide a valuable model for addressing fundamental scientific questions about molecular wires. [31][32][33][34][35][36] The ferrocenyl group, a widely applicable organometallic scaffold, well-known for its excellent redox activity and synthetic versatility, 37 has been incorporated into the spacer unit of T-S-T ligands (1a-c and 2a and 2b, Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48] The luminescence properties of organometallic compounds in solution are well-documented. [9][10][11][49][50][51][52][53][54][55][56][57][58][59] The inclusion of transition metal moieties gives access to efficient spin-orbit coupling, which, in turn, enables the population of excited states of triplet character and phosphorescence characteristics of organometallic compounds. As such the coordination of the organic compounds to metal centers can enrich the emission properties by enabling access to new excited-state species.…”
Section: Introductionmentioning
confidence: 99%
“…This study recognized first the phenomenon of room-temperature luminescence of this type of Ru 2+ complex. The Dong group has undertaken systematic studies of the electrochemical and photophysical properties to probe the electronic states of complexes containing bis(2,2′:6′,2′′-terpyridine)polyferrocene redox-active spacers that are end-capped with photoactive Ru 2+ -terpyridine terminals. They have found that the insertion of an ethynyl group into the main chain can lead to an increase in the excited-state lifetimes.…”
Section: Introductionmentioning
confidence: 99%